Perceptions of Physician Order Entry: Results of a Cross-Site Qualitative Study - Ash, J. S.; Gorman, P. N.; Lavelle, M.; Stavri, P. Z.; Lyman, J.; Fournier, L.; Carpenter, J. (Methods of Information in Medicine, 2003)
Objective: To identify perspectives of success factors for implementing computerized physician order entry (POE) in the inpatient setting.Design: Qualitative study by a multidisciplinary team using data from observation, focus groups, and both formal and informal interviews. Data were analyzed using a grounded approach to develop a taxonomy of patterns and themes from the transcripts and field notes.Results: A taxonomy of ten high level themes was developed, including 1) separating POE from other processes, 2) terms, concepts, and connotations, 3) context, 4) tradeoffs, 5) conflicts and contradictions, 6) collaboration and trust, 7) leaders and bridgers, 8) the organization of information, 9) the ongoing nature of implementation, and 10) temporal concerns.Conclusion: The identified success factors indicate that POE implementation is an iterative and difficult process, but informants perceive it is worth the effort.
Keywords: Physician order entry; clinical systems; qualitative study; qualitative research methods